Expertise and emotion: how online opinion leaders shape public perceptions of AI—among university students in China - Liu, Wenjun; Jiang, Yi’an; Deng, Weijia; Tan, Aibo (Frontiers in Communication, 2025)
The rapid development of AI technology has triggered intense discussions on social media. As key users, online opinion leaders (OILs) wield “emotional power” that exhibits an “emotion setting” effect, influencing users’ perceptions of AI, with their “expert” identity playing a crucial role in emotional communication. To examine the impact of OILs’ expert credibility and emotional arousal level on users’ AI perception, an experimental study (N = 102) was conducted. Results show that under a negative tone, higher-expert-credibility OILs led participants to perceive AI as more useful (PU) and easier to use (PEOU). Similarly, higher emotional arousal strengthened these perceptions. Notably, for high-credibility OILs, the arousal-credibility interaction significantly affected both PEOU and PU, whereas for low-credibility OILs, it impacted PU but not PEOU. Furthermore, AI anxiety mediates the arousal-perception relationship, moderated by expert credibility. Critically, emotional arousal significantly influenced AI anxiety regardless of credibility level. This study elucidates how OILs shape sociotechnical imaginaries amid rapid AI advancement.